(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
Set theory is a fundamental branch of mathematics that deals with the study of sets, their operations, and the relationships between them. A set is defined as a collection of distinct objects, and set theory provides the formal framework for understanding how these collections interact. This article explores the foundational concepts of set theory, including set operations, relations, and their significance in mathematics. It also discusses key results in the theory, such as the Axiom of Choice, the Zermelo-Fraenkel axioms, and the concept of cardinality, as well as the role of set theory in other mathematical fields.